2014
DOI: 10.1007/s10096-014-2243-3
|View full text |Cite
|
Sign up to set email alerts
|

Solar radiation and water vapor pressure to forecast chickenpox epidemics

Abstract: The clear seasonality of varicella infections in temperate regions suggests the influence of meteorologic conditions. However, there are very few data on this association. The aim of this study was to determine the seasonal pattern of varicella infections on the Mediterranean island of Mallorca (Spain), and its association with meteorologic conditions and schooling. Data on the number of cases of varicella were obtained from the Network of Epidemiologic Surveillance, which is composed of primary care physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…A possible explanation for this might be that longer periods of sunshine correspond to higher doses of solar radiation. Hervás et al [ 33 ] found that the effects of solar radiation, directly on the host immune system and/or indirectly through vitamin D metabolism, may play a role in varicella epidemics [ 32 ]. Another possible explanation for this might be that longer periods of sunshine correspond to more time for human activities outdoors where exposure to VZV is more likely.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this might be that longer periods of sunshine correspond to higher doses of solar radiation. Hervás et al [ 33 ] found that the effects of solar radiation, directly on the host immune system and/or indirectly through vitamin D metabolism, may play a role in varicella epidemics [ 32 ]. Another possible explanation for this might be that longer periods of sunshine correspond to more time for human activities outdoors where exposure to VZV is more likely.…”
Section: Discussionmentioning
confidence: 99%
“…Specific models have been designed for diseases such as measles,[ 7 ] rubella, chickenpox,[ 8 ] dengue fever,[ 9 ] whooping cough,[ 10 ] smallpox,[ 11 ] malaria,[ 12 ] HIV/AIDS [ 13 ] and others. [ 14 ] Most models take the basic reproduction number R0 of the causative agent, defined as the threshold quantity that determines when an infection can invade and persist in a new host population, as one of the main assets.…”
Section: Introductionmentioning
confidence: 99%
“…School closure, on the other hand, has been demonstrated to decrease respiratory morbidity during an influenza outbreak in Israel (Heymann et al in 2004). Likewise, an inverse association was observed between the number of varicella cases and school holidays in Mallorca (Spain) (Hervás et al 2015). However, the impact of schooling on bacterial infections is less known, and the association between GAS pharyngitis and schooling has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%